Efektivitas Pemberian Eco Enzyme Terhadap Pertumbuhan Generatif Tanaman Padi (Oryza sativa L.) Varietas Lampai Sirandah Kabupaten Sijunjung - Khusnul Khatimah; Kiki Amelia; Resti Fevria (UNIVERSITAS LABUHANBATU, 2026)
Eco enzyme is an organic solution resulting from the fermentation of organic waste, sugar and water. Eco enzyme liquid is dark in color and has souroma.Materials to make eco enzyme can come from organic waste such as fruit peels,vegetables, and others, and the fermentation process takes about three months. This study aims to determine the right dose of eco enzyme for the growth of Lampai Sirandah rice variety in Sijunjung Regency. The study used a group randomized design with 5 treatment levels and 5replications, a total of 25 experimental units. The treatments given were without eco enzyme, 20 ml/l water, 40 ml/l water, 60 ml/l water, and 80 ml/l water. Based on the results of the study, the application of eco enzyme showed a significant effect on the flower emergence, number of panicles, panicle length, harvest age, number of grains per clump. The best dose of eco enzyme to increase the vegetative growth of Lampai Sirandah rice plants in Sijunjung Regency is 60ml/l water (P3). Keywords: lampai sirandah rice, eco enzyme